TREATMENT OF ATOPIC DERMATITIS IN CHILDREN WITH BIOAPIFIT® ANTIINFLAMATORY HERBAL OINTMENT - A PRELIMINARY STUDY - Oreščanin, Višnja (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
Objectives: The purpose of this work was development, formulation and testing of new herbalointment for the treatment of mild to severe atopic dermatitis in infants and children (4 to 56 monthsold) as possible alternative therapy to standard corticosteroids and immunomodulants.Patients and methods: 50 patients were treated 8 weeks (every four hours) with the ointmentcontaining the following ingredients: Avena sativa, Nigella sativa, Argania spinosa, Prunus amygdalus,Daucus carota, Helichrysum italicum, Calendula officinalis, Matricaria chamomilla, Bellis perennis,Lavandula officinalis, Achillea millefolium,Thymus serpyllum, Salvia officinalis, Symphytumofficinale, Plantago major, Olea europaea, Melaleuca alternifolia, Cera alba, honey, and glycerol. Theseverity of the disease prior and after the therapy was assessed by SCORAD index.Results: The total score before the therapy ranged from 23.1 to 99.4 (66.50±23.43). Among the testedpatients 76%, 20% and 4% had severe, moderate and mild symptoms, respectively. Following the eightweeks treatment the extent, intensity and subjective symptoms decreased significantly. The totalscore decreased more than 20 times compared to the initial values and ranged from 0 to 14(13.18±4.29). The intensity parameters (swelling, oozing/crusting and scratch marks) as well assubjective parameters (itch and sleeplessness) disappeared completely following two months therapy.Conclusion: Two months of the topical treatment with Bioapifit® herbal anti-inflammatory ointmentresulted in complete remission of the symptoms in 56% of the patients while in another 44% of themonly mild symptoms persisted. Such excellent results could be atributed to the ointment’s formulationcontaining emollients, strong anti-inflammatory, immunomodulating, wound healing and antimicrobialagents of herbal origin that simultaneously targeted the multiple mechanisms involved in ADpathogenesis. This ointment could be used as alternative therapy to the topical corticosteroids andimmunomodulants.